Narrative analysis of Jonas’s book from Paul Ricoeur’s mimetic process - Gonçalves, Luciene Lima (2021)
In this article the book of Jonas is approached, by the narrative method, using the mimetic process of Paul Ricoeur, from the triple mimesis: prefiguration, configuration and refiguration. The purpose of this article is to highlight the importance of this type of approach for illuminating a specific character of Jonas’ text that is obscured in most of the reflections elaborated on this book: that of manifesto literature. For this, Jonas’s text is analyzed considering its four chapters, which correspond to narrative frames, mainly through refiguration, that is, through the reader’s eyes. Thus, it is concluded that this method favors the understanding of the book both in its condition of literature and its theology.